Perivascular macrophage‐like melanocyte responsiveness to acoustic trauma—a salient feature of strial barrier associated hearing loss. Issue 9 (31st May 2013) - Zhang, Fei; Dai, Min; Neng, Lingling; Zhang, Jin Hui; Zhi, Zhongwei; Fridberger, Anders; Shi, Xiaorui
Abstract : Tissue perivascular resident macrophages (PVM/Ms), a hybrid cell type with characteristics of both macrophages and melanocytes, are critical for establishing and maintaining the endocochlear potential (EP) required for hearing. The PVM/Ms modulate expression of tight‐ and adherens‐junction proteins in the endothelial barrier of the stria vascularis (intrastrial fluid‐blood barrier) through secretion of a signaling molecule, pigment epithelium growth factor (PEDF). Here, we identify a significant link between abnormalities in PVM/Ms and endothelial barrier breakdown from acoustic trauma to the mouse ear. We find that acoustic trauma causes activation of PVM/Ms and physical detachment from capillary walls. Concurrent with the detachment, we find loosened tight junctions between endothelial cells and decreased production of tight‐ and adherens‐junction protein, resulting in leakage of serum proteins from the damaged barrier. A key factor in the intrastrial fluid‐blood barrier hyperpermeability exhibited in the mice is down‐regulation of PVM/M modulated PEDF production. We demonstrate that delivery of PEDF to the damaged ear ameliorates hearing loss by restoring intrastrial fluid‐blood barrier integrity. PEDF up‐regulates expression of tight junction‐associated proteins (ZO‐1 and VE‐cadherin) and PVM/M stabilizing neural cell adhesion molecule (NCAM‐120). These studies point to the critical role PVM/Ms play in regulating intrastrial fluid‐blood barrier integrity in healthy and noise‐damaged ears.—Zhang, F., Dai, M., Neng, L., Zhang, J.H., Zhi, Z., Fridberger, A., Shi, X., Perivascular macrophage‐like melanocyte responsiveness to acoustic trauma—a salient feature of strial barrier associated hearing loss. FASEB J. 27, 3730–3740 (2013). www.fasebj.org